THE FACTORS OF EUROPEAN CULTURAL POLICY IN THE COUNCIL OF EUROPE RECOMMENDATION “ON HISTORY TEACHING IN TWENTY-FIRST-CENTURY EUROPE” - Tarasenko, Oleksandra (SWorld-Ger Conference proceedings, 2025)
This study focuses on analyzing the Council of Europe Recommendation on the Teaching of History in the Twenty-First Century in Europe, examining it within the context of the European Union’s broader cultural policies. The focus is on the importance of add